Síntese de LiFePO4 em sistema hidrotermal assistido por micro-ondas, caracterização e testes como catodo de baterias de íons lítio - Bezerra, Carlos André Gomes (Universidade Federal de São Carlos, 2018)
Different routes for lithium iron phosphate (LiFePO4) synthesis were studied in a microwave-assisted hydrothermal system in order to reduce the time and temperature of synthesis in relation to the traditional methods of obtaining this compound. For the synthesis of LiFePO4 different mixtures of precursor materials were investigated maintaining the molar ratio Li: Fe: P = 3: 1: 1. In the step of time and synthesis temperature optimization, heating times of 5 to 40 min and temperatures of 100 to 200 °C were investigated. Based on the structural characterization results, by Fourier transform infrared spectroscopy and X-ray diffractometry, it was found that from 10 min at 200 °C it was possible to obtain pure and crystalline LiFePO4, with particle size of 57 to 165 nm, verified by scanning electron microscopy micrographs. Cyclic voltammetry for the five best samples showed the typical voltammetric profile of the LiFePO4 with good reversibility; three of the samples selected showed high electrochemical activity, which was reflected in good values of specific capacity. In the characterization by electrochemical impedance spectroscopy, an inversely proportional relation between total impedance and values of specific capacity was verified. The sample with the best electrochemical performance presented a value of 168 mA h g-1, at discharge rate of C/10, corresponding to 99% of the specific theoretical capacity of LiFePO4. A capacity retention of 74% was verified after 100 cycles of charge - discharge at C/2, which was related to the electrolyte contamination by water, attributed to the presence of moisture in the chamber where the electrochemical cells were assembled.
Microwave-assisted hydrothermal synthesis of LiFePO4, characterization and tests as cathodes for lithium ion batteries
Keywords: LiFePO4; Sintese hidrotermal assistida por micro-ondas; Baterias de íons lítio; Materias catódicos; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA